Extended suspect screening to identify contaminants of emerging concern in riverine and coastal ecosystems and assessment of environmental risks - Čelić, Mira (2021)
A suspect screening methodology was developed for the fast and reliable identification of 360 contaminants of emerging concern (CECs) of anthropogenic origin in the vulnerable area of the Ebro Delta (Catalonia, Spain) and to track for potential contamination sources. The suspect screening methodology was combined with a risk assessment approach to prioritize the most ecologically relevant CECs. Out of the 360 suspects, 37 compounds were tentatively identified, 22 of which were fully confirmed using isotopically labelled standards. The detected suspect compounds included pesticides, pharmaceuticals, personal care products, stimulants and their metabolites. Pesticides were more ubiquitous in irrigation and drainage channels, while pharmaceuticals, stimulants, and personal care products were the most common in effluent wastewaters, in the receiving freshwater systems as well as in the marine environment. Ten compounds were found to be of high ecological concern, including the pharmaceuticals telmisartan, venlafaxine, and carbamazepine, the herbicides terbuthylazine, desethylterbuthylazine, and terbutryn, the fungicides azoxystrobin, tebuconazole and prochloraz and the insecticide tebufenozide. These compounds could be used as markers of anthropogenic contamination in riverine and coastal ecosystems.